Pharmacological and non-pharmacological treatments for neuropathic pain: Systematic review and French recommendations - Moisset, X.; Bouhassira, D.; Avez Couturier, J.; Alchaar, H.; Conradi, S.; Delmotte, M.H.; Lanteri-Minet, M.; Lefaucheur, J.P.; Mick, G.; Piano, V.; Pickering, G.; Piquet, E.; et al. (Revue neurologique, 2020)
•SNRI/tricyclic antidepressants and gabapentin are recommended first line for NP.•Topical lidocaine and TENS are recommended first line for peripheral NP.•Pregabalin is now recommended second line.•Psychotherapy is recommended second line as add-on to other therapies.•rTMS and spinal cord stimulation (select conditions) are third line. Neuropathic pain remains a significant unmet medical need. Several recommendations have recently been proposed concerning pharmacotherapy, neurostimulation techniques and interventional management, but no comprehensive guideline encompassing all these treatments has yet been issued. We performed a systematic review of pharmacotherapy, neurostimulation, surgery, psychotherapies and other types of therapy for peripheral or central neuropathic pain, based on studies published in peer-reviewed journals before January 2018. The main inclusion criteria were chronic neuropathic pain for at least three months, a randomized controlled methodology, at least three weeks of follow-up, at least 10 patients per group, and a double-blind design for drug therapy. Based on the GRADE system, we provide weak-to-strong recommendations for use and proposal as a first-line treatment for SNRIs (duloxetine and venlafaxine), gabapentin and tricyclic antidepressants and, for topical lidocaine and transcutaneous electrical nerve stimulation specifically for peripheral neuropathic pain; a weak recommendation for use and proposal as a second-line treatment for pregabalin, tramadol, combination therapy (antidepressant combined with gabapentinoids), and for high-concentration capsaicin patches and botulinum toxin A specifically for peripheral neuropathic pain; a weak recommendation for use and proposal as a third-line treatment for high-frequency rTMS of the motor cortex, spinal cord stimulation (failed back surgery syndrome and painful diabetic polyneuropathy) and strong opioids (in the absence of an alternative). Psychotherapy (cognitive behavioral therapy and mindfulness) is recommended as a second-line therapy, as an add-on to other therapies. An algorithm encompassing all the recommended treatments is proposed.